2018
DOI: 10.1016/j.ijvsm.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of nanotechnology in male fertility and sperm function

Abstract: Recent advances in nanotechnology have tremendously expanded its possible applications in biomedicine. Although, the effects of nanoparticles (NPs) at cellular and tissue levels have not been fully understood, some of these biological effects might be employed in assisted reproduction to improve male fertility particularly by enhancing sperm cell quality either in vivo or in vitro. This review summarises the available literature regarding the potential applications of nanomaterials in farm animal reproduction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 81 publications
(93 reference statements)
2
49
0
1
Order By: Relevance
“…Nanotechnology, such as nano-zinc and nano-selenium, can be used to achieve bioactive properties in the reproduction, digestion, development, and freezing cells of various elements [78]. Recent studies have shown the beneficial effects of nanoparticles for sperm freezing in humans and animals by lowering the sperm chromatin damage and MDA levels [79][80][81]. However, no studies have examined the impact of zinc oxide or selenium nanoparticles on epididymal camel sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology, such as nano-zinc and nano-selenium, can be used to achieve bioactive properties in the reproduction, digestion, development, and freezing cells of various elements [78]. Recent studies have shown the beneficial effects of nanoparticles for sperm freezing in humans and animals by lowering the sperm chromatin damage and MDA levels [79][80][81]. However, no studies have examined the impact of zinc oxide or selenium nanoparticles on epididymal camel sperm.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the synthesized iron oxide particles measured 7 to 14 nm in diameters, and corresponded to maghemite (γ-Fe 2 O 3 ) and hematite (α-Fe 2 O 3 ) as revealed by the HRTEM images showing respective interplanar distances of 2.54 Å and 2.98 Å [41, 42]. All forms of MNP (hematite or α-Fe 2 O 3 , maghemite or γ-Fe 2 O 3 , and magnetite or Fe 3 O 4 ) have been used for in vitro targeting of spermatozoa, in a broad range of applications (i.e., sperm nanopurification, toxicity test, and sperm-mediated gene transfer), without affecting their functionality or structures (reviewed by [43]). In the current study, the conjugation of maghemite-made MNP with annexin V and hematite-made MNP with lectins (PNA/LCA) to respectively target apoptici and acrosome reacted spermatozoa [4446] did not affect the MNP magnetism nor the functionality of both MNP conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…Darbandi et al () reported that lifestyle and environmental factors might be major contributing factors to the rising incidence of male infertility. The scientific community is also increasingly wary of the deleterious effects of nanomaterials on the reproductive system, especially of males (Falchi, Khalil, Hassan, & Marei, ). This current study, therefore, assessed the potential reproductive toxicity of VERN following 14‐days repeated dose administration in male albino rats.…”
Section: Discussionmentioning
confidence: 99%